Workload of official contests, net cost of transport, and metabolic power of Mangalarga Marchador horses of marcha batida or picada gaits - Lage, J. [UNESP]; Fonseca, M. G. [UNESP]; de Barros, G. G.M.; Feringer-Júnior, W. H. [UNESP]; Pereira, G. T. [UNESP]; Ferraz, G. C. [UNESP] (Oxford University Press (OUP), 2017)
This study aimed to characterize the maximum heart rate (HRMAX) and the intensity of official marcha contests (OMC) and to compare the cost of transport (COT) and metabolic power (Pmet) of Mangalarga Marchador (MM) horses of marcha batida (MB) and marcha picada (MP) gaits. Twenty-two MM horses participated in this study. The experiment was conducted in 3 phases: 1) maximum effort test (MET), 2) OMC, and 3) standardized marcha test (SMT). To characterize the HRMAX, 19 horses (14 MB and 5 MP) underwent a MET. Of those, 13 (9 MB and 4 MP) were monitored during the OMC, which consisted of 4 stages: marcha, walk, functional trial, and rest. The average heart rate (HR) in each stage of the OMC was related to the HRMAX to determine their relative intensity. The SMT was performed with 14 horses (9 MB and 5 MP), of which 11 had already participated in the previous stages. The COT and Pmet were calculated from the HR values obtained during the SMT. Blood samples were collected to analyze plasma lactate concentration ([Lac]). One-way ANOVA or 1-way repeated-measures ANOVA followed by the Tukey’s test (P < 0.05) were used to analyze the results. The average HRMAX was 211 ± 11 and 214 ± 11 beats/ min (bpm) for the MB and MP groups, respectively, with no difference (P = 0.7066) between them. The [Lac] increased as a result of the MET (P < 0.05), with no difference between groups (P > 0.05). This indicated that horses of both groups had the same physical fitness levels. The OMC stages defined in our study differed (P < 0.05) regarding the relative intensity of the HRMAX, except for the walk and standing stages, which were similar (P = 0.0875). The MP group presented greater COT (P = 0.0247) and Pmet (P = 0.0193). It can be concluded that the mean HRMAX of MM horses (MB and MP) is 212 ± 11 bpm. The OMC of the MM breed can be characterized as an effort of intermittent and submaximal intensity. In addition, the locomotion of the MB horses is probably more energetically efficient than that of MP horses.
Keywords: Energy metabolism; Equine; Gaited horses; Heart rate; Lactate; Mangalarga marchador